The effect of the method of production a new fertilizer containing Streptomyces coelicolor grown on whey on its effectiveness - E. I. Magradze (Овощи России, 2025)
Relevance. In recent years, we have seen an increase in the number of new bacterial fertilizers. New fertilizers must be effective, so it is important to select their qualitative and quantitative composition. It is equally important to study the effect of these bacteria on their number, dissemination and long-term residence in the soil, as well as their effects on plants.Aim of the Study. This work studies the effect of the method of obtaining a fertilizer containing Streptomyces coelicolor grown on the whey on the amount and duration of these bacteria in the soil and on the growth characteristics of white mustard (Sinapis alba L.) sown into the soil after a long time after watering with fertilizer.Methods. The whey was diluted and autoclaved, Streptomyces coelicolor were grown on this substrate. An inoculum for this biofertilizer was obtained in two ways. The first way: Streptomyces coelicolor were grown once on a Waksman`s media. The second way: the inoculum was sequentially grown on the whey, gradually increasing the volume. Bacteria in fertilizer were cultivated without mixing or by mixing in the temperature-controlled shaker. We studied the effect of biofertilizer on soil in containers in the laboratory. The amount of Streptomyces coelicolor in the soil was determined 0.5, 1.5, 2 and 4 months after watering by fertilizer. Seeds of white mustard were sown two months after watering with fertilizer. We studied the effect of fertilizer on growth characteristics of white mustard.Results. The fertilizer obtained by sequentially cultivating the inoculum and growing streptomyces without mixing contained ten times more streptomyces than fertilizers obtained by another method. This biofertilizer also effectively increased the number of streptomyces in the soil. Streptomyces from fertilizer have been preserved in the soil for a long time. The effect of biofertilizers obtaining without mixing on growth characteristics of white mustard was the most effectively.Conclusion. The fertilizer obtained by sequentially cultivating the inoculum and growing streptomyces without mixing contributes to a more increase of streptomyces number in the soil and is more effective in growing white mustard then fertilizers obtained by other methods. Our biofertilizer is effective in growing crops sown in the soil for a long time after watering with fertilizer. The fertilizer can be used in indoor crop production and greenhouse farms.